Analisis Tingkat Kematangan Kompos Campuran Limbah Padat Kelapa Sawit dengan Penambahan Bioaktivator - Sylvia Madusari (JURNAL CITRA WIDYA EDUKASI, 2017)
Oil Palm Plantations have various types of solid waste and liquid waste. Solid waste produced in the form of midrib and fiber, while the liquid waste is oil palm mill effluent (POME). The amount of waste that is abundant has the potential for waste buildup. Composting solid waste is an alternative solution to increase the added value of waste so it can be used again. The purpose of this study was to compare two commercial activators and palm oil mill effluent to the maturity level of the mixture of midrib and fiber. The research method was performed with Completely Randomized Design with five treatments, namely: PM1 (50% midrib + 50% fiber + cow dung + Activator A); PM2 (50% midrib + 50% fiber + cow dung + Activator B); PM3 (50% midrib + 50% fiber + cow dung + POME); PM4 (50% midrib + 50% fiber + Activator B); PM5 (50% midrib + 50% fiber + POME). Observation parameters, ie measurement of temperature, pH, conductivity, nutrient content of compost, cellulolytic microbial count and hemicellulose and cellulose content. The results showed that the temperature at each treatment had a significant effect on the 1st week. At the end of observation the highest highest temperature was found at PM1 which was 27.630C and the lowest in PM4 was 27,34 0C. The highest pH was in PM3 treatment (8.7) and lowest in PM2 (5.16). The highest conductivity values ​​were in PM2 treatment (1.40 mS.cm-1) and lowest PM5 (0.26 mS.cm-1). The highest C / N ratio of PM4 was 13.98 and the lowest was PM3 8. It is necessary to further test the utilization of compost as planting medium and as a soil enhancer.